Day of Week and Surgery Location Effects on Stay Length and Cost for Total Joint Arthroplasty: Academic versus Orthopaedic-Specific Hospital - Martino, John; Peterson, Blake; Thompson, Samuel; Cook, James L.; Aggarwal, Ajay (The Journal of Knee Surgery, 2018)
Demand for total hip (THA) and knee arthroplasties (TKA) is expected to rise sharply by 2030. Increasing demand in conjunction with financial pressure requires the use of cost-effective total joint arthroplasty (TJA) strategies. This study examined the effects that day of week and surgery location [academic (AH) versus orthopaedic-specific (OsH) hospital] have on length of stay (LOS) and cost for primary TJA patients in one multihospital university-based medical center. An Institutional Review Board-approved database of adult patients undergoing primary THA or TKA from June 2013 to December 2014 was constructed. Surgery location, day of procedure, age, American Society of Anesthesiologists (ASA) classification, LOS, and cost were recorded for each patient. Data were compared for significant differences using analysis of variance, t-Test or rank sum and for strength of correlations using Pearson's or Spearman's tests. A total of 1,291 patients met inclusion criteria. OsH showed significantly lower cost and shorter LOS than AH. Wednesday surgeries had significantly higher cost and longer LOS than all other days. Friday surgeries had significantly lower cost and shorter LOS than other days. ASA 3 and 4 were associated with the highest cost and longest LOS. LOS had a moderately strong direct correlation to cost. ASA did not have a strong correlation with LOS or cost. Data separated for THA and TKA showed similar results. At our institution, OsH provides more consistent and lower LOS and cost across all ASA classes. Wednesday and Thursday surgeries have increased LOS and cost than other days, which may be due to weekend discharge difficulties (average LOS is 3.0 days).
Keywords: total joint arthroplasty; length of stay; cost; day of the week